DESAIN PORTAL KAMPUS SELULER DI LINGKUNGAN BIG DATA - Totok Mulyono (Jurnal Teknologi dan Terapan Bisnis, 2019)
The development of smart mobile devices and big data technology and mobile applications has become an efficient tool for sharing information. This mobile learning system provides an interactive teaching platform between lecturers and students. Learners can study online classes at any time and anywhere with the help of mobile devices. This research proposes a mobile learning application to Android and Blackberry smart phones. The mobile application provides e-learning services on the client side for students and sharing service interface on the service side. The concept of big data uses volume, variety, velocity, veracity and value or abbreviated as 5V. This research explains why and how to design a mobile campus portal to meet the requirements of the education big data environment, introduce the topology, applications and structure of the mobile portal campus system and discuss the implementation of the 5V big data concept on the mobile portal campus. This study applies the concept of 5V big data in designing an effective mobile campus portal. The final results of Mobile Campus Portal research at the application level provide five types of application modules for users including teaching management, administrative management, financial management, research management and public services. In meeting the requirements of the big data environment on campus, the Mobile Campus Portal applies the five dimensions of the big data concept to the entire data processing cycle. Data integration uses volume and dimension variations. Data translation uses the speed dimension and the data security control uses the truth and authentication dimension. Data mining uses the value dimension.